Acculturation and self-rated health among Chinese and Korean immigrants aged 49 to 75 - Ryu, Soomin; Morey, Brittany N.; Shi, Yuxi; Lee, Sunmin (Frontiers in Public Health, 2023)
Background Given the rapidly growing Asian populations in the U.S. due to immigration, and the aging demographic of Asian immigrants, it is crucial to understand how acculturation shapes health among older adult Asian immigrants. We study the relationship between acculturation and self-rated health (SRH) and moderating roles of age and Asian subgroup. Methods Our cross-sectional study consisted of 200 Chinese and 200 Korean immigrants aged 49–75 living in Baltimore–Washington DC metropolitan area, who were recruited from primary care physicians' clinics in Maryland and Northern Virginia. The participants completed the survey either in-person or by phone in their preferred language. Multidimensional proxies were used to measure acculturation: years living in the U.S. (≥23 years, <23 years), English proficiency (fluently/well, so-so, poorly/not at all), and ethnic identity (very Asian, mostly Asian, bicultural/westernized). SRH was measured using the question “How would you rate your general health?” (excellent/very good/good, fair/poor). Poisson regression models with robust error variance examined associations between acculturation and SRH, accounting for socioeconomic and health insurance factors. Results Speaking English so-so and fluently/well had 0.73 (95% confidence intervals (CI): 0.55–0.97) and 0.51 (95% CI: 0.30–0.87) times the prevalence of having fair or poor SRH compared to speaking English poorly/not at all, respectively. The magnitudes and statistical significance of these associations were stronger among Chinese participants than Korean participants. Moreover, individuals who self-identified as bicultural/westernized had 0.63 times the prevalence of having fair or poor SRH (95% CI: 0.43–0.92) as those who self-identified as very Asian. The association was more pronounced among older participants (≥58) compared to younger participants (<58). Conclusion Further research should identify the possible mechanisms linking acculturation with health to find effective strategies to enhance health among aging Asian immigrant populations.